Back to Basics: Emphasizing Grammar in the ESL Classroom - Wee, Kim Peck (INTI University College, 2007)
The Information era is here and advances in technology have dramatically improved the way ¡n which we can communicate electronically. Worldwide communication is now made possible with the explosion of the Internet. Given this scenario, the ability to communicate concisely and accurately has become even more crucial. In the last 10-15 years, many language educationists have expressed concern over the declining mastery level of the English Language among undergraduates at our local universities. Time and again, we hear of graduates failing to secure jobs due to their weak communication skills and poor command of English. Many job advertisements usually have at least one of the following as part of their requirements: • able to write and speak English fluently • able to make effective presentations • able to prepare/write reports • able to communicate well